2017
DOI: 10.3390/w9020085
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Pharmaceuticals from Wastewater by Intermittent Electrocoagulation

Abstract: Abstract:The continuous release of emerging contaminants (ECs) in the aquatic environment, as a result of the inadequate removal by conventional treatment methods, has prompted research to explore viable solutions to this rising global problem. One promising alternative is the use of electrochemical processes since they represent a simple and highly efficient technology with less footprint. In this paper, the feasibility of treating ECs (i.e., pharmaceuticals) using an intermittent electrocoagulation process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 67 publications
0
22
0
3
Order By: Relevance
“…pH, temperature, and ORP were obtained using a multiparametric probe (HQ40d). The degree of mineralization of the Acetamiprid was ascertained by measuring the chemical oxygen demand (COD) according to standard methods (Ensano et al 2017 ). Also, the by-products resulting from decomposition of acetamiprid were analyzed by gas chromatography–mass (GC–MS) (Wang and Shih 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…pH, temperature, and ORP were obtained using a multiparametric probe (HQ40d). The degree of mineralization of the Acetamiprid was ascertained by measuring the chemical oxygen demand (COD) according to standard methods (Ensano et al 2017 ). Also, the by-products resulting from decomposition of acetamiprid were analyzed by gas chromatography–mass (GC–MS) (Wang and Shih 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…The biorecalcitrant pollutants, such as PCs, are only removed partially by the conventional wastewater treatment processes (Kanakaraju et al, 2018;Luján-Facundo et al, 2019), accordingly, advanced techniques are needed to achieve a complete degradation of these persistent contaminants. Among the various new technologies have been developed (Mashayekh-Salehi and Moussavi, 2016;Ensano et al, 2017;Radjenović et al, 2009;Shariati et al, 2010;Escolà Casas et al, 2015;Tambosi et al, 2010), ozone based-advanced oxidation processes (AOPs) are recommended for water treatment in view of PCs removal (Klavarioti et al, 2009;Feng L., 2014). Previous studies have shown that the use of sole ozonation process (SOP) has great advantages in removing odor and color, however is not particularly effective in eliminating PCs (Saeid et al, 2018;Wang and Bai, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many methods, such as chemical treatment, ltration, activated sludge, reverse osmosis, electrocoagulation, and advanced oxidation process, have been employed for the removal of paracetamol from contaminated water. [5][6][7][8] Among the advanced oxidation (AO) processes, light-driven photocatalytic degradation has received considerable attention due to its costeffectiveness, eco-friendly nature, and the absence of residual secondary pollutants. 9,10 Therefore, the modication or synthesis of novel photocatalysts for this purpose is a prime concern in the eld of AO.…”
Section: Introductionmentioning
confidence: 99%